Composition and sensory properties of sour cherry cultivars - Bánáti, D.; Tóth-Markus, M.; Adányi, N.; Boross, F.; Vámos-Falusi, Zs.; Daood, H. G.; Szabó, T.; Nyéki, J. (International Journal of Horticultural Science, 2010)
Fruits of different sour cherry varieties cultivated, in 2008 and 2009, under organic farming and integrated cultivation conditions were analysed for their quality attributes, antioxidant activity and subjected to sensory evaluation.. Average size, weight, soluble solids, titratable acidity, total polyphenols, free radical scavenging capacity expressed as Trolox equivalent (TEAC), copper and zinc were determined in freshly harvested fruits. The obtained results indicated that, the principal component analysis can separate and distinguish the seasons of fruit production. The farming system seemed to have slight effect on quality the fruit as compared to varietal factors (genotypes). However, the total polyphenol content was uniformly less in 2009. Total polyphenols and free radical scavenging activity were significantly higher in Bosnian type sour cherries, and outstanding in Amarelle type cultivar ‘Pipacs’. There was no statistically significant difference between the sensory properties of cultivars tested by panels, except the case of ‘Pipacs’. The organolaptic investigation showed marked preference to the fruits of Eva and Petri cultivars.